Kegiatan Pengabdian Masyarakat: Penapisan Kolesterol Total dalam Upaya Pencegahan Penyakit Jantung Koroner pada Usia Produktif - Frisca, Frisca; Santoso, Alexander Halim; Destra, Edwin; Suros, Angel Sharon; Sarijuwita, Alicia (Jurnal Pengabdian West Science, 2025)
High total cholesterol is a significant risk factor for coronary heart disease, especially in the productive age population. Early detection of cholesterol levels plays an important role in reducing the risk of health complications that can occur. This community service activity was carried out using the Plan-Do-Check-Act (PDCA) method which focused on health education and total cholesterol screening in 40 productive age individuals, aiming to increase awareness of the importance of cholesterol control. The education provided included information on risk factors for increased cholesterol, such as a diet high in saturated fat and lack of physical activity, as well as preventive measures that can be applied. Screening was carried out to detect individuals with high cholesterol levels so that appropriate preventive measures could be taken. The average total cholesterol level of participants was 224.55 mg/dL, with an average age distribution of 43.97 years. Counseling can increase participants' understanding of the risks of high cholesterol and the importance of a healthy lifestyle to maintain cholesterol levels. Education and screening of total cholesterol are expected to increase participants' awareness of the risks of high cholesterol and the importance of prevention through lifestyle changes. It is hoped that this activity can reduce the risk of cholesterol-related complications in the productive age group.